2020
DOI: 10.3329/jbcbm.v5i2.44920
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton flora of Tanguar Haor ecosystem of Bangladesh: Chlorophyta

Abstract: The qualitative and quantitative aspects of phytoplankton population belonging to the green algae (Chlorophyta) from Watch Tower and Rauar Station of Tanguar Haor, Sunamganj were studied. In the study, a total of 39 species of three Orders under the algal Division Chlorophyta was worked out. Their photomicrographs and individual densities in the pelagic community of phytoplankton over a study year of 2016 and 2017 are discussed. In Volvocales, Volvox carteri Stein, in Chlorococcales, Coelastrum microporum Näge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Eudorina sp., Pleuodorina sp., Pandorina morum, Dictyosphaerium pulchellum, Coelastrum microporum, Closterium kuetzingianum var. kuetzingianum, Pediastrum duplex and Fragilaria virescens were found common in occurrence in both the Haor Ecosystems (4)(5) .…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Eudorina sp., Pleuodorina sp., Pandorina morum, Dictyosphaerium pulchellum, Coelastrum microporum, Closterium kuetzingianum var. kuetzingianum, Pediastrum duplex and Fragilaria virescens were found common in occurrence in both the Haor Ecosystems (4)(5) .…”
Section: Resultsmentioning
confidence: 94%
“…The latter compound was recorded >1.0 mg/l, except the Rauar Station of Tanguar Haor. Bhuiyan et al (2)(3)(4)(5) observed the mean water transparency 2.51 m, SRP 17.19 µg/l and chl-a 5.47 in Tanguar Haor (2)(3)(4)(5) , while the measurements carried out in the Hakaluki Haor during the fish kill event were: water transparency 1.24 m, SRP 12.50 µg/l and chl-a 38.05 µg/l. Tanguar Haor has a relatively deeper basin compared to Hakaluki and holding little clearer water, as it is evident by the data on Secchi Disc value and chl-a measured for both the Haors.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The excessive pollution of Tanguar Haor has recently drawn the attention of scientists from Bangladesh [14,15]. Previously, a number of studies has been conducted in Tanguar Haor regarding biodiversity [7,[16][17][18][19], birds [20], aquatic plants [21], water quality [17], radioactivity [15], and ecosystem management [22,23]. However, none of them focused on heavy metal contamination or its ecological risk to inhabitants.…”
Section: Introductionmentioning
confidence: 99%